A Combination of Anadara nodifera Shell and Milkfish Thorns Powder Effectively Promote Springiness Index, Serum Testosterone, and Breast Muscle Testosterone in Bangkok Rooster - Akhmad Abror As Sidiqi; Claude Mona Airin; Sarmin Sarmin; Pudji Astuti (HAYATI Journal of Biosciences, 2023)
Aromatase blocker effectively promotes testosterone, which improves muscle performance and protein synthesis. Considerable muscle strength in Bangkok rooster is the outcome of testosterone activity. Clamshell contains aromatase blocker substances, while fishbone possesses a high amount of protein. This research aimed to evaluate the clamshell and fishbone combination potency towards testosterone levels and muscle performance in Bangkok roosters. This study employed 18 Bangkok roosters under 35 days of treatment. The rooster groups consisted of control (P0, n = 6); clamshell-fishbone (P1, n = 6): clamshell (6.6 gram/day) + fishbone (3.3 gram/day); fishbone (P2, n = 6): fishbone (3.3 gram/day). The blood was collected once every seven days. Enzyme immunoassay showed the highest serum and muscle testosterone levels in P1 (p<0.05). Immunohistochemistry presented the most and broadest myofiber and the highest proliferation activity in P1 (p<0.05). The texture analysis showed the topmost springiness index in P1 (p<0.05). Aromatase blockers in clamshell and protein in fishbone improve testosterone and muscle performance in Bangkok roosters.